Shelter efficiency of Dalbergia sissoo Roxb. shelterbelt in IGNP command area in arid Western Rajasthan, India - Prasad, Rajendra; Mertia, R.S.; Kumawat, R.N.; Samra, J.S. (Indian Journal of Agroforestry, 2020)
The study was conducted to assess shelter efficiency of single-row and double-row Dalbergia sissoo based shelterbelt in IGNP command area in Mohangarh, Jaisalmer district of arid Western Rajasthan. The findings revealed that the double-row shelterbelt had provided more effective sheltered area (upto distance of eight times height of shelterbelt: 8H) than that provided by single-row (up to distance of four times height of shelterbelt: 4H) on leeward side of tree-belt. Presence of shelterbelt improved soil characteristics and modified air temperature in sheltered area. Improvement in soil organic carbon and reduction in air temperature was more pronounced at distance of two times of shelterbelt height (2H) and leveled off up to distance of five times height (5H) of the shelterbelt on leeward side. The height, foliage density and length of shelterbelt are decisive for tunneling effects at both ends of shelterbelts. It is inferred that the double-rowÂ Dalbergia sissoo based shelterbelt of 15-20 years age having 8-10 m height hold great promise for moderating microclimate and providing effective shelter to crops against wind borne hazards in arid areas.